A novel intronic variant in UBE3A identified by genome sequencing in a patient with an atypical presentation of Angelman syndrome. Issue 9 (11th July 2020) - Curtis, Meredith; Baribeau, Danielle; Walker, Susan; Carter, Melissa; Costain, Gregory; Lamoureux, Sylvia; Liston, Eriskay; Marshall, Christian R.; Reuter, Miriam S.; Snell, Meaghan; Summers, Jane; Vorstman, Jacob; et al.
Abstract: Angelman syndrome (AS) is a genetic neurodevelopmental disorder caused by loss or deficient expression of UBE3A on the maternally inherited allele. In 10–15% of individuals with a clinical diagnosis of AS, a molecular diagnosis cannot be established with conventional testing. We describe a 13‐year‐old male with an atypical presentation of AS, who was found to have a novel, maternally inherited, intronic variant in UBE3A (c.3‐12T>A) using genome sequencing (GS). Targeted sequencing of RNA isolated from blood confirmed the creation of a new acceptor splice site. These GS results ended a six‐year diagnostic odyssey and revealed a 50% recurrence risk for the unaffected parents. This case illustrates a previously unreported splicing variant causing AS. Intronic variants identifiable by GS may account for a proportion of individuals who are suspected of having well‐known genetic disorders despite negative prior genetic testing.